Analisis perhitungan dan pemungutan pajak hotel dan pajak restoran pada Badan Pengelola Pajak dan Retribusi Daerah Kabupaten Kepulauan Talaud - Manggaribet, Widya Devi; Runtu, Treesje; Suwetja, I Gede (Riset Akuntansi dan Portofolio Investasi, 2025)
Regional Taxes are divided into two categories, namely Provincial Taxes and Regency/City Taxes. Hotel Tax and Restaurant Tax are included in the regional tax category. This study aims to analyze the calculation and collection of hotel tax and restaurant tax at the Regional Tax and Retribution Management Agency of the Talaud Islands Regency. This type of research is qualitative descriptive research. Data were obtained using documentation and interview methods. The results of the study indicate that the collection/receipt of hotel tax and restaurant tax fluctuates. Taxpayer compliance which is still very low affects the decoration and collection of taxes as well as the contribution of hotel tax and restaurant tax to the Regional Original Income of the Talaud Islands Regency. The Regional Tax and Retribution Management Agency of the Talaud Islands Regency must impose strict sanctions on taxpayers who are found to be non-compliant in paying taxes.